Spin dynamics of radical pairs in magnetic fields - Luo, J (2022)
The remarkable ability of migratory birds to use the geomagnetic field for their navigation has been fascinating scientists for more than 50 years. Extensive studies, from experiments to theories, suggest that avian magnetoreception may arise from photo-induced radical-pair reactions in the birds’ eyes. Although the energy for the interaction of a single molecule with a magnetic field as weak as ∼50 μT is more than a million times smaller than the thermal energy, such weak fields can still significantly influence spin-selective reactions via the modulation of radical-pair spin dynamics.